The improvement of tax control in the conditions of digitalization - I. A. Tsindeliani; Т. A. Guseva; A. V. Izotov (Правоприменение)
The subject. The features of the improvement of tax control and tax enforcement in the conditions of digitalization.The purpose of the article is to identify features and trends of the improvement of tax control and tax enforcement in the conditions of digitalization. The methodology includes systematic approach, comparative method, formal-logical method, formal-legal method, analysis, synthesis.The main results of the research. The article identifies the main directions of development of law enforcement activities of tax authorities and tax legal relations in the context of digitalization. The specifics of the development of intra-organizational analytical approaches to tax control, as well as trends in the transformation of tax legal relations have been established. Tax legal relations arising from tax control, while improving the intra-organizational analytical approaches of tax authorities, do not have significant changes due to the preservation of classical forms of control. Digitalization involves improving tax administration and increasing the efficiency of law enforcement activities of tax authorities.Conclusions. Improving the law enforcement activities of tax authorities within legal relations arising in the implementation of tax control is associated, on the one hand, with the creation and development of effective intra-organizational control and analytical approaches, and on the other hand, with the transformation and differentiation of tax legal relations themselves. In the first area, tax legal relations are not subject to significant changes. In the second area, the transformation of tax legal relations entails changes in the system of rights and obligations of tax authorities, implemented in law enforcement.